Vitamin D Status in Patients of Gestational Diabetes Mellitus in Comparison to That of Normal Pregnancy (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Although the role of vitamin-D in calcium metabolism and bone health is undisputed, other long-term health consequences of low vitamin-D are still debated. Observational studies have recently indicated that vitamin-D deficiency may be a modifiable risk factor for gestational diabetes mellitus (GDM), although several experimental studies have failed to establish such an association. The present study was undertaken to test the hypothesis that vitamin-D insufficiency or deficiency is associated with GDM.Methods: The present case-control study was conducted in the Department of Obstetrics and Gynaecology, Rajshahi Medical College (RMC), Rajshahi, Bangladesh, over a period of 1 year between July 2019 to June 2020. Patients with confirmed GDM (case) and normal pregnant women (control) attending in the above-mentioned place during the study period were the study population. A total of 18 cases and 54 controls were consecutively included in the study based on predefined eligibility criteria. The exposure and outcome variables were serum vitamin-D insufficiency/deficiency and GDM respectively. Vitamin D insufficiency was considered when serum level 25(OH)D ranges from ≥ 15 to < 30 ng/ml and deficiency was termed if 25(OH)D level lies below 15 ng/ml. Crosstab analysis with Odds Ratio (OR) was done to find the association between vitamin-D and GDM and the risk of developing the outcome (GDM) due to vitamin-D insufficiency or deficiency.Result: In the present study age, residence, socioeconomic status and season at data collection were almost identically distributed between case and control groups. However, the study demonstrated occupation, pre-pregnancy obesity, family history of type-II diabetes, polyhydramnios, level of hemoglobin and serum vitamin-D insufficiency/deficiency to be associated with GDM. Majority (83.3%) of the GDM patients had insufficient or deficient serum vitamin D level (< 30 ng/mL) as compared to 57.4% of the control group. The risk of having GDM in pregnant women with insufficient or deficient serum vitamin-D was estimated to be almost 4-fold (95% CI = 1.1 – 14.3) higher (p = 0.047) than that in the pregnant women with normal serum vitamin-D level.Conclusion: The study concluded that pregnant women with GDM are associated with insufficient or deficient serum vitamin-D with risk of having GDM in pregnant women with insufficient or deficient serum vitamin-D is much greater than the pregnant women with normal serum vitamin-D level.Ibrahim Card Med J 2021; 11 (1): 41-47